THE PERCEPTUAL MAPPING OF NOTEBOOK BRANDS OF YOUNG PEOPLE IN MANADO - Tampinongkol, Devid Christian; Saerang, David P.E; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2017)
Abstract: Most products and services have many physical and intangible attributes with varied characteristics for a would-be purchaser. For example, toothpaste is not merely